Public–private partnerships for improved service delivery: the case of Intercity STC Coaches in Ghana. Issue 1 (2nd January 2021) - Damoah, Clement Mensah; Asamoah, Kwame
ABSTRACT: This article assesses how the public–private partnership involving Intercity STC Coaches in Ghana has impacted on service delivery. An exploratory qualitative research approach was adopted for the study. The key findings indicate that the PPP has helped Intercity STC Coaches to increase the number of fleets, although these are still considered inadequate. Additionally, Intercity STC Coaches' clients are satisfied with the services rendered to them. The article, therefore, recommends that Intercity STC Coaches should look for more investors to procure additional buses so as to meet the growing demand from their clients.